The Cambridge introduction to twentieth-century American poetry - Beach, Christopher (Cambridge University, 2013)
The Cambridge Introduction to Twentieth-Century American Poetry is designed to give readers a brief but thorough introduction to the various movements, schools, and groups of American poets in the twentieth century. It will help readers to understand and analyze modern and contemporary poems.